A NARRATIVE REVIEW OF PRECISION MEDICINE, ARTIFICIAL INTELLIGENCE, AND THE FUTURE OF PERSONALIZED CARE: REVOLUTIONIZING HEALTHCARE. - S.K. Prasad (Student’s Journal of Health Research Africa, 2023)
Background The merging of AI and precision medicine is a paradigm change in healthcare. Precision medicine uses patient-specific traits to adapt medical interventions, while AI improves decision-making with advanced computational approaches. This convergence considers genetic and nongenomic characteristics, patient symptoms, clinical history, and lifestyle to address precision medicine difficulties. Objective This narrative review explores the potential of AI in advancing precision medicine. It examines the synergy between AI and precision medicine, emphasizing their combined capacity to enable individualized diagnosis and prognosis for patients with unique healthcare requirements or atypical responses to treatments. Summary of Narrative Review Recent literature underscores the promise of AI in precision medicine through translational research. AI’s computational power allows it to analyze vast datasets, identify patterns, and generate valuable insights. By integrating genomic and nongenomic determinants with clinical and lifestyle data, AI enhances the accuracy and effectiveness of diagnosis and prognosis. This review delves into the transformative potential of this convergence, highlighting its applications in healthcare decision-making and patient care. Implications for Future Research Future research should focus on further developing AI-driven precision medicine tools and platforms. Investigating the real-world clinical impact of AI-driven precision medicine is essential, along with evaluating the scalability, ethical considerations, and regulatory frameworks for its implementation. Additionally, exploring AI’s potential in optimizing treatment plans, drug discovery, and healthcare resource allocation is a crucial avenue for future research. Clinical Practice and Policy Development The amalgamation of AI and precision medicine offers healthcare professionals augmented intelligence, empowering them to make more informed decisions tailored to individual patient needs. This has the potential to improve treatment outcomes, reduce adverse effects, and enhance patient care. Policymakers and healthcare institutions should consider investing in AI-driven precision medicine initiatives and establishing guidelines for data privacy, ethics, and patient consent to ensure its responsible and ethical implementation.